LOW-TEMPERATURE NUCLEAR ORIENTATION ON THE KONDO SYSTEM CEXND1-XNI - Oliveira, I; Nishimura, K; Stone, N; Isikawa, Y; Zakoucky, D; Doran, D (1994)
The isotope Nd147 has been oriented by means of low-temperature nuclear orientation on the pseudobinary series CexNd1-xNi for x=0.0, 0.1, 0.25, 0.5, and 0.8. The results show that the compounds are magnetically ordered due to Nd-Nd interactions and no magnetic moment exists on cerium. The Kondo effect is present (for x 0) as revealed by measurements of electical resistivity and thermoelectric power. © 1994 The American Physical Society.